2016
DOI: 10.1111/nyas.13219
|View full text |Cite
|
Sign up to set email alerts
|

Extraskeletal actions of vitamin D

Abstract: The vitamin D receptor (VDR) is found in nearly all, if not all, cells in the body. The enzyme that produces the active metabolite of vitamin D and ligand for VDR, namely CYP27B1, likewise is widely expressed in many cells of the body. These observations indicate that the role of vitamin D is not limited to regulation of bone and mineral homeostasis, as important as that is. Rather, the study of its extraskeletal actions has become the major driving force behind the significant increase in research articles on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(125 citation statements)
references
References 296 publications
(320 reference statements)
2
110
0
7
Order By: Relevance
“…The effects of vitamin D on calcium homoeostasis and its importance for skeletal health are well‐known . In recent times, there has been an increased focus on nonskeletal effects of vitamin D, following the discovery of vitamin D receptors (VDRs) and the vitamin D activating enzyme 1‐alfa‐hydroxylase in extraskeletal tissues . Observational studies have reported associations between higher serum 25‐hydroxyvitamin D (25(OH)D) levels and lower risk of multiple pathological conditions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of vitamin D on calcium homoeostasis and its importance for skeletal health are well‐known . In recent times, there has been an increased focus on nonskeletal effects of vitamin D, following the discovery of vitamin D receptors (VDRs) and the vitamin D activating enzyme 1‐alfa‐hydroxylase in extraskeletal tissues . Observational studies have reported associations between higher serum 25‐hydroxyvitamin D (25(OH)D) levels and lower risk of multiple pathological conditions .…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, there has been an increased focus on nonskeletal effects of vitamin D, following the discovery of vitamin D receptors (VDRs) and the vitamin D activating enzyme 1‐alfa‐hydroxylase in extraskeletal tissues . Observational studies have reported associations between higher serum 25‐hydroxyvitamin D (25(OH)D) levels and lower risk of multiple pathological conditions . It is of note, however, the general lack of data from randomized controlled trials (RCTs) confirming the positive effects hypothesized from the descriptive studies …”
Section: Introductionmentioning
confidence: 99%
“…In these settings, calcitriol regulates multiple cellular processes, effecting normal and malignant cell growth and differentiation, innate immune function, and cardiovascular function. Unlike the renal enzyme, the extrarenal CYP27B1 expression is regulated by specific local factors, receiving feedback from locally expressed CYP27B1 and CYP24A1 and also available calcidiol [8]. …”
Section: Vitamin D Physiologymentioning
confidence: 99%
“…6,33 Although there are many different causative pathologies, both kidney disease and eventual graft failure are associated with inflammation and fibrosis, the latter characterized by excess connective tissue deposition. 2,34,35 Chronic injury leads to scarring with excessive myofibroblast proliferation and consequent production of ECM proteins, particularly collagens.…”
Section: Discussionmentioning
confidence: 99%